2018
DOI: 10.3892/or.2018.6661
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MYU promotes prostate cancer proliferation by mediating the miR-184/c-Myc axis

Abstract: Long non-coding RNAs (lncRNAs) play critical roles in tumorigenesis and cancer progression. The c-Myc upregulated lncRNA MYU (VPS9D1 antisense RNA1, annotated as VPS9D1-AS1) has been reported in several common types of human cancers, which has revealed that lncRNA MYU could function as either an oncogene or a tumor-suppressor gene in different cancer types. However, the function of lncRNA MYU in prostate cancer remains unknown. In the present study, we demonstrated that lncRNA MYU is significantly upregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 38 publications
4
39
0
Order By: Relevance
“…Changes in the expression of the lncRNA VPS9D1-AS1 have been observed in several malignant tumors, including gastric [23], prostate [24], and colorectal [25] cancers. Expression of VPS9D1-AS1 is upregulated in NSCLC and closely associated with clinical outcome [26].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the expression of the lncRNA VPS9D1-AS1 have been observed in several malignant tumors, including gastric [23], prostate [24], and colorectal [25] cancers. Expression of VPS9D1-AS1 is upregulated in NSCLC and closely associated with clinical outcome [26].…”
Section: Introductionmentioning
confidence: 99%
“…These exosomal lncRNAs are significantly enriched in target motifs for the miRs, which are found in the same exosomes, suggesting that the sorting of exosomes is a highly organized process that allows for the selection of specific miRs and lncRNAs to be uploaded in their vesicles [184]. It has been reported that exosome-associated lncRNA MYU induces adjacent PCa cell proliferation and migration by competitively binding to miR-184 and therefore upregulates c-Myc [185]. Moreover, urine-derived exosomes collected from PCa patients are enriched in lncRNA-p21, which is associated with the malignancy of PCa [186].…”
Section: The Role Of Exosomes In Shuttling Bioactive Materials Betweementioning
confidence: 99%
“…Affect osteoclastogenesis and osteoblastogenesis and help PCa cells to overcome androgen deprivation in long distant metastasis [180,181,188,189] miR-409, miR-379 and miR-154 Support PCa carcinogenesis and metastasis [177] miR-485-3p Associated with fludarabine resistance in PCa cells [190] H-ras, K-ras (mRNA) Neoplastic transformation of PC patients' adipose stem cells. [130] LincRNA-p21 (lncRNA) Associated with PC malignancy [186] lncRNA MY (lncRNA) Promote adjacent cell proliferation and migration [185] 3.7. Two-Way Crosstalk between Stromal Cells and PCA Cell-Associated Exosomal Cargo…”
Section: Nucleic Acid(s) Biological Function Reference(s)mentioning
confidence: 99%
“…Furthermore, VPS9D1-AS1 level was related to gastric cancer patients' disease-free survival rate (Chen et al, 2017). However, compared with normal prostate tissue or lung tissue, VPS9D1-AS1 was significantly upregulated in cancerous prostate tissue or cancerous non-small cell lung tissue (Wang et al, 2018;Han et al, 2020). These studies showed that VPS9D1-AS1 had different roles in different diseases.…”
Section: Introductionmentioning
confidence: 96%